Technical Change and Superstar Effects: Evidence from the Rollout of Television - Felix Koenig (Institute of Labor Economics (IZA), 2021)
Technical change that extends market scale can generate winner-take-all dynamics, with large income growth among top earners. I test this "superstar model" in the entertainer labor market, where the historic rollout of television creates a natural experiment in scale-related technological change. The resulting inequality changes are consistent with superstar theory: the launch of a local TV station skews the entertainer wage distribution sharply to the right, with the biggest impact at the very top of the distribution, while negatively impacting workers below the star level. The findings provide evidence of superstar effects and distinguish such effects from popular alternative models.
Keywords: J31; J23; O33; D31; 330; superstar effect; inequality; top incomes; technical change